Is higher education curriculum prepare to support sustainable environmental chemistry learning? - Mellyzar, Mellyzar; Nahadi, Nahadi; Rochintaniawati, Diana; Riandi, Riandi; Hernani, Hernani; Supriatna, Asep; Lee, Tien Tien (Education and Development Research, 2025)
Global environmental challenges such as climate change, pollution, and ecosystem degradation require urgent responses, and education plays a strategic role in building environmental literacy. This study aimed to evaluate the readiness of higher education curricula in supporting sustainable learning in Environmental Chemistry courses and their alignment with the Sustainable Development Goals (SDGs). The research used a descriptive approach involving curriculum and lesson plan analysis, student surveys, and interviews with lecturers and program heads at a state university in Aceh Province, Indonesia. The findings show that while the curriculum includes relevant topics such as pollution and climate change, the integration of emerging issues and practical learning methods remains limited. Students demonstrated positive attitudes and awareness toward environmental sustainability, but their active involvement in practical actions was still low. Recommendations include the explicit integration of SDGs in course plans, diversification of teaching strategies through fieldwork and case studies, and fostering interdisciplinary collaboration. Overall, the study concludes that the curriculum provides a strong foundation but requires strategic improvements to enhance its relevance and impact. Aligning academic programs with global and local environmental challenges will enable higher education to prepare students as proactive agents of sustainable development.